2020
DOI: 10.3390/biom10070995
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Alleviates Anxiety, Motor, and Cognitive Dysfunctions in Rats with Maternal Hyperhomocysteinemia via Mitigation of Oxidative Stress

Abstract: Hydrogen sulfide (H2S) is endogenously produced from sulfur containing amino acids, including homocysteine and exerts neuroprotective effects. An increase of homocysteine during pregnancy impairs fetal growth and development of the offspring due to severe oxidative stress. We analyzed the effects of the H2S donor—sodium hydrosulfide (NaHS) administered to female rats with hyperhomocysteinemia (hHcy) on behavioral impairments and levels of oxidative stress of their offspring. Rats born from females fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 107 publications
1
13
0
Order By: Relevance
“…In addition, the CA3 and DG areas of the hippocampus participate in spatial learning and memory, which are important for the maintenance of hippocampal function. Furthermore, it has been demonstrated that HMD reduces the neurons number in the CA3 and DG [ 52 , 53 ], suggesting that these data help to understand the impact of HMD on changes in the nervous system. Although these effects are consistent with our results, they did not clarify the relationship between HMD-induced AD-like symptoms and 5-mC as in this work.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the CA3 and DG areas of the hippocampus participate in spatial learning and memory, which are important for the maintenance of hippocampal function. Furthermore, it has been demonstrated that HMD reduces the neurons number in the CA3 and DG [ 52 , 53 ], suggesting that these data help to understand the impact of HMD on changes in the nervous system. Although these effects are consistent with our results, they did not clarify the relationship between HMD-induced AD-like symptoms and 5-mC as in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the redox status of NMDARs may govern the contribution of GluN2A and GluN2B subunit-containing receptors to HCY-caused neurotoxicity, which is an unexpected conclusion. This observation can provide some clues as to why treatment with reducing reagents like hydrogen sulfide (H 2 S) rescues NMDAR expressing neuroblastoma cells [ 44 ], neurons [ 45 ], and prevents behavioral alterations [ 46 ] in hyperhomocysteinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Also 3-mercaptopyruvate sulfurtransferase (MPST) is involved in brain H 2 S synthesis from 3-mercaptopyruvate (3-MPT). Of note, an interesting crosstalk between NO and CO pathways may regulate heme moiety of CBS has recently been suggested [ 107 109 ]. A non-enzymatic reaction of H 2 S synthesis which is catalyzed by pyridoxal 5′-phosphate (vitamin B6) and iron may also occur in some tissues especially within erythrocytes [ 110 ].…”
Section: Neural and Glial H 2 S Biosynthesis And Mmentioning
confidence: 99%